Change in autoantibody and cytokine responses during the evolution of neuromyelitis optica in patients with systemic lupus erythematosus: A preliminary study. (August 2016) - Kovacs, Katalin T; Kalluri, Sudhakar Reddy; Boza-Serrano, Antonio; Deierborg, Tomas; Csepany, Tunde; Simo, Magdolna; Rokusz, Laszlo; Miseta, Attila; Alcaraz, Nicolas; Czirjak, Laszlo; Berki, Timea; Molnar, Tihamer; et al.
Background: Neuromyelitis optica (NMO)–systemic lupus erythematosus (SLE) association is a rare condition characterized by multiple autoantibodies. Objective: To examine if, during the evolution of NMO, anti-AQP4 responses are part of polyclonal B cell activation, and if T cell responses contribute. Methods: In 19 samples of six patients who developed NMO during SLE, we examined the correlation of AQP4-IgG1 and IgM with (i) anti-MOG IgG and IgM, (ii) anti-nuclear, anti-nucleosome and anti-dsDNA IgG antibodies, (iii) cytokines and chemokines in the serum and (iv) longitudinal relation to NMO relapses/remission. Results: AQP4-IgG1 was present 1–2–5 years before the first NMO relapse. During relapse, AQP4-IgG1, ANA, anti-dsDNA and anti-nucleosome antibodies were elevated. Anti-MOG IgG/IgM and AQP4-IgM antibodies were not detected. AQP4-IgG1 antibodies correlated with concentration of anti-nucleosome, IFN-γ, interferon-gamma-induced CCL10/IP-10 and CCL17/TARC ( p <0.05, respectively). CCL17/TARC correlated with levels of anti-nucleosome and anti-dsDNA ( p <0.05, respectively). Compared to healthy subjects, concentration of IFN-γ and CCL17/TARC was higher in NMO/SLE ( p <0.05). Conclusions: AQP4-IgG1 antibodies are present in the sera years before the first NMO attack in patients with SLE; elevation of anti-AQP4 is part of a polyclonal B cell response during NMO relapses; in spite of multiple autoantibodies in the serum, MOG antibodies were not present; Th1 responses accompany autoantibody responses in NMO/SLE.